Focused ultrasound in ophthalmology - Silverman RH (Clinical Ophthalmology, 2016)
Ronald H Silverman1,2 1Department of Ophthalmology, Columbia University Medical Center, 2F.L. Lizzi Center for Biomedical Engineering, Riverside Research, New York, NY, USA Abstract: The use of focused ultrasound to obtain diagnostically significant information about the eye goes back to the 1950s. This review describes the historical and technological development of ophthalmic ultrasound and its clinical application and impact. Ultrasound, like light, can be focused, which is crucial for formation of high-resolution, diagnostically useful images. Focused, single-element, mechanically scanned transducers are most common in ophthalmology. Specially designed transducers have been used to generate focused, high-intensity ultrasound that through thermal effects has been used to treat glaucoma (via cilio-destruction), tumors, and other pathologies. Linear and annular transducer arrays offer synthetic focusing in which precise timing of the excitation of independently addressable array elements allows formation of a converging wavefront to create a focus at one or more programmable depths. Most recently, linear array-based plane-wave ultrasound, in which the array emits an unfocused wavefront and focusing is performed solely on received data, has been demonstrated for imaging ocular anatomy and blood flow. While the history of ophthalmic ultrasound extends back over half-a-century, new and powerful technologic advances continue to be made, offering the prospect of novel diagnostic capabilities. Keywords: ophthalmic ultrasound, ultrasound biomicroscopy (UBM), high-intensity focused ultrasound (HIFU), ultrafast imaging, Doppler imaging